A Minimally Invasive Method for Observing Wind-Up of Flexion Reflex in Humans: Comparison of Electrical and Magnetic Stimulation - Taniguchi, Tomoya; Kinukawa, Tomoaki Alex; Takeuchi, Nobuyuki; Sugiyama, Shunsuke; Nishihara, Makoto; Nishiwaki, Kimitoshi; Inui, Koji (Frontiers in Neuroscience, 2022)
Wind-up like pain or temporal summation of pain is a phenomenon in which pain sensation is increased in a frequency-dependent manner by applying repeated noxious stimuli of uniform intensity. Temporal summation in humans has been studied by observing the increase in pain or flexion reflex by repetitive electrical or thermal stimulations. Nonetheless, because the measurement is accompanied by severe pain, a minimally invasive method is desirable. Gradual augmentation of flexion reflex and pain induced by repetitive stimulation of the sural nerve was observed using three stimulation methods—namely, bipolar electrical, magnetic, and monopolar electrical stimulation, with 11 healthy male subjects in each group. The effects of frequency, intensity, and number of repetitive stimuli on the increase in the magnitude of flexion reflex and pain rating were compared among the three methods. The reflex was measured using electromyography from the short head of the biceps femoris. All three methods produced a frequency- and intensity-dependent progressive increase in reflex and pain; pain scores were significantly lower for magnetic and monopolar stimulations than for bipolar stimulation (P < 0.05). The slope of increase in the reflex was steep during the first 4–6 stimuli but became gentler thereafter. In the initial phase, an increase in the reflex during the time before signals of C-fibers arrived at the spinal cord was observed in experiments using high-frequency stimulation, suggesting that wind-up was caused by inputs of A-fibers without the involvement of C-fibers. Magnetic and monopolar stimulations are minimally invasive and useful methods for observing the wind-up of the flexion reflex in humans. Monopolar stimulation is convenient because it does not require special equipment. There is at least a partial mechanism underlying the wind-up of the flexion reflex that does not require C-fibers.